Substance Use Among Homeless Individuals With Schizophrenia and Bipolar Disorder. Issue 3 (March 2017) - Maremmani, Angelo G.I.; Bacciardi, Silvia; Gehring, Nicole D.; Cambioli, Luca; Schütz, Christian; Jang, Kerry; Krausz, Michael
Abstract : Abstract: Mental illness and substance use are overrepresented within urban homeless populations. This paper compared substance use patterns between homeless individuals diagnosed with schizophrenia spectrum (SS) and bipolar disorders (BD) using the Mini-International Neuropsychiatric Interview. From a sample of 497 subjects drawn from Vancouver, Canada who participated in the At Home/Chez Soi study, 146 and 94 homeless individuals were identified as BD and SS, respectively. In the previous 12 months, a greater proportion of BD homeless reported greater use of cocaine ( χ 2 = 20.0, p = 0.000), amphetamines ( χ 2 = 13, 8, p = 0.000), opiates ( χ 2 = 24.6, p = 0.000), hallucinogens ( χ 2 = 11.7, p = 0.000), cannabinoids ( χ 2 = 5.05, p = 0.034), and tranquilizers ( χ 2 = 7.95, p = 0.004) compared to SS. Cocaine and opiates were significantly associated with BD homeless ( χ 2 = 39.06, df = 2, p < 0.000). The present study illustrates the relationship between substance use and BD in a vulnerable urban population of homeless, affected by adverse psychosocial factors and severe psychiatric conditions.